A comparison of estrus synchronization with Syncro-Mate-B® to natural service - C. Middleton; T. Brink; G. Kiracofe; J. Brethour; R. Negus (Kansas Agricultural Experiment Station Research Reports, 1985)
Conception rates and subsequent calving dates were compared between cows synchronized with Syncro-Mate-B® and inseminated by appointment and nonsynchronized cows bred by natural service. Average conception date was seven days earlier in the synchronized cows.
Keywords: Cattlemen' s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Estrus; Synchronization